Seeds get around - White, Nancy (New York : Newbridge Communications, 1993)
Discover that plants grow both from seeds we plant and from those that are carried by wind, water, animals, car tires, even by themselves!
K-3.
Keywords: Oversize books -- Specimens; Seeds; Big books; Seeds